ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA DAN PERKEMBANGAN SAHAM SYARI’AH DI INDONESIA - Eka Sri Wahyuni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Eka Sri Wahyuni; The purpose of this study was to determine the factors - factors that affect stock prices and the development of Shari'ah in Indonesia. The method used in this library research. The results in this study is the movement of the stock price is affected by many factors. There are micro factors, there are also macro. In addition, the factors that affect stock price consists of fundamentals and technical factors. The fundamental factors are very important, because the share price is highly correlated with the company's ability to create future profits for shareholders. While technical factors are stock prices affected by movements in the share purchase price, number of shares traded and other data sourced from the market. Both fundamental and technical factors used as a quantitative analysis to determine the previous data on interest rates, economic variables and the value of stocks. This analysis is very important for investors to make a decision to invest in shares.Key Word: Stock Price Sharia, Islamic Shares Number of Transactions